PENGARUH BERAT DAN WAKTU KONTAK UNTUK ADSORPSI TIMBAL(II) OLEH ADSORBEN DARI KULIT BATANG JAMBU BIJI (Psidium guajava L.) - Sri Lestari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2010)
Research about influence of weight and contact times of to adsorb lead(II) by adsorbent from bark of guava has been done. The research was varied by series of adsorbent weight 0.5; 1.0; 1,5; 2.0; 2.5; and 3.0 gram and the contact time 30, 60, 90, 120, 150, and 180 minutes. Concentration of lead(II) in sample is measured by atomic absorption spectrophotometer. The result showed that optimum contact time is 90 minutes. It was also found that higher adsorbent weight will increase the total amount of adsorbed lead(II).Keywords: Adsorption, lead(II), bark, guava